Authoritarian populism and emancipatory politics in the rural United States. (February 2021) - Roman-Alcalá, Antonio; Graddy-Lovelace, Garrett; Edelman, Marc
Highlights: The Democratic Party's neoliberal turn alienated its working-class base. A white-washed version of "the rural" drives ethno-nationalist populism in the USA. Historical and contemporary cases of multiracial unity deserve greater attention. Internal colonialism is key to analyzing racial formation and urban/rural divides. Uncertainty, when recognized as a shared problem, can build solidarity.